Restoring invisible and abandoned trials of gabapentin for neuropathic pain: a clinical and methodological investigation. Issue 6 (30th June 2021) - Mayo-Wilson, Evan; Chen, Xiwei; Qureshi, Riaz; Dickinson, Stephanie; Golzarri-Arroyo, Lilian; Hong, Hwanhee; Görg, Carsten; Li, Tianjing
Abstract : Introduction: Gabapentin (Neurontin) is prescribed widely for conditions for which it has not been approved by regulators, including certain neuropathic pain conditions. There is limited evidence that gabapentin is safe and effective for the treatment of neuropathic pain. Published trial reports, and systematic reviews based on published trial reports, mislead patients and providers because information about gabapentin's harms has been published only partly. We confirmed that trials conducted by the drug developer have been abandoned, and we plan to conduct a restoration with support from the Restoring Invisible and Abandoned Trials Support Centre (https://restoringtrials.org/ ). Methods and analysis: In this study, we will analyse and report the harms that were observed in six trials of gabapentin, which have not been reported publicly (eg, in journal articles). We will use clinical study reports and individual participant data to identify and report the harms observed in each individual trial and to summarise the harms observed across all six trials. We will report all adverse events observed in the included trials by sharing deidentified data and summary tables on the Open Science Framework (https://osf.io/w8puv/ ). Additionally, we will produce a summary report that describes differences between the randomised groups in each trial and across trials for prespecified harms outcomes. Ethics and dissemination: We will use secondary data. This study was determined to be exempt from Institutional Review Board (IRB) review (protocol #1910607198).